Research Techniques Made Simple: Analysis of Collective Cell Migration Using the Wound Healing Assay - Grada, Ayman; Otero-Vinas, Marta; Prieto-Castrillo, Francisco; Obagi, Zaidal; Falanga, Vincent (Journal of investigative dermatology, 2017)
Collective cell migration is a hallmark of wound repair, cancer invasion and metastasis, immune responses, angiogenesis, and embryonic morphogenesis. Wound healing is a complex cellular and biochemical process necessary to restore structurally damaged tissue. It involves dynamic interactions and crosstalk between various cell types, interaction with extracellular matrix molecules, and regulated production of soluble mediators and cytokines. In cutaneous wound healing, skin cells migrate from the wound edges into the wound to restore skin integrity. Analysis of cell migration in vitro is a useful assay to quantify alterations in cell migratory capacity in response to experimental manipulations. Although several methods exist to study cell migration (such as Boyden chamber assay, barrier assays, and microfluidics-based assays), in this short report we will explain the wound healing assay, also known as the "in vitro scratch assay" as a simple, versatile, and cost-effective method to study collective cell migration and wound healing.